2021
DOI: 10.3390/jfmk6040096
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Exercise: Adaptations and Applications for Health and Performance

Abstract: The goals of this narrative review are to provide a brief overview of the muscle and tendon adaptations to eccentric resistance exercise and address the applications of this form of training to aid rehabilitative interventions and enhance sports performance. This work is centered on the author contributions to the Special Issue entitled “Eccentric Exercise: Adaptations and Applications for Health and Performance”. The major themes from the contributing authors include the need to place greater attention on ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The use of progressive eccentric exercise has been proposed for the treatment of a variety of chronic diseases such as tendinopathies [ 1 ], coronary artery disease [ 2 ], knee osteoarthritis [ 3 ] or for the preservation of muscle mass in chronic obstructive pulmonary disease patients [ 4 ]. The implementation of eccentric contractions as a part of resistance training program has also been shown to be beneficial for the improvement of athletic performance through gain of muscle mass, strength, and power [ 5 7 ] and useful as an injury prevention/rehabilitation strategy [ 8 ]. Despite the benefits of this type of exercise, lengthening contractions can alter the ultrastructure of the muscle tissue and induce exercise-induced muscle damage (EIMD) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of progressive eccentric exercise has been proposed for the treatment of a variety of chronic diseases such as tendinopathies [ 1 ], coronary artery disease [ 2 ], knee osteoarthritis [ 3 ] or for the preservation of muscle mass in chronic obstructive pulmonary disease patients [ 4 ]. The implementation of eccentric contractions as a part of resistance training program has also been shown to be beneficial for the improvement of athletic performance through gain of muscle mass, strength, and power [ 5 7 ] and useful as an injury prevention/rehabilitation strategy [ 8 ]. Despite the benefits of this type of exercise, lengthening contractions can alter the ultrastructure of the muscle tissue and induce exercise-induced muscle damage (EIMD) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was reported that eccentric muscle contractions were more effective for improving neuromuscular activation, strength, and walking speed than concentric contractions ( 69 ). The reason for that is explained where eccentric muscle contraction leads to the generation of greater force while requiring less motor unit activation, and consumes less oxygen and energy for a given muscle force compared to concentric and isometric contractions leading to adaptations ( 69 , 70 ). Hence, it is beneficial in gaining strength with less energy cost compared to other resistive training such as concentric or isometric contractions ( 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…High mechanical loads are in general recognized to stimulate muscle hypertrophy [ 23 ] as well as positive adaptations to passive tissue [ 24 , 25 ]. The performance-related benefits of high eccentric loads specifically, such as during the braking phase of repetitive squat jumps, were demonstrated in a novel study by Hori et al These authors suggested that eccentric loading during jump training plays an important role for improving concentric force at high movement velocities, whereas this is not the case for improvements at slower velocities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%